2004
DOI: 10.1103/physrevlett.92.017402
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Donors in Diamond: Chalcogens, Pnictogens, and their Hydrogen Complexes

Abstract: The utility of diamond as an electronic material is compromised by the lack of a suitable shallow donor. Here, ab initio theory is used to investigate the donor levels of substitutional pnictogen (N, P, As, and Sb) and chalcogen (S, Se, and Te) impurities and chalcogen-hydrogen defects in diamond. Substitutional S is found to be a deep donor, while As and Sb possess donor levels significantly shallower than P, which so far is the most effective shallow donor found by experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 42 publications
1
56
0
2
Order By: Relevance
“…Other dopants have also been tried, such as sulphur and arsenic [90], however no systematic results have been obtained so far. A complex involving boron and hydrogen complex has recently been proposed as a shallow dopant for n-type diamond [91] but the long-term stability of the complex is still not known.…”
Section: Diamond Dopingmentioning
confidence: 99%
“…Other dopants have also been tried, such as sulphur and arsenic [90], however no systematic results have been obtained so far. A complex involving boron and hydrogen complex has recently been proposed as a shallow dopant for n-type diamond [91] but the long-term stability of the complex is still not known.…”
Section: Diamond Dopingmentioning
confidence: 99%
“…The substrate had an area of 1×1 cm 2 and made from an intrinsic (undoped) single crystal (100) Si wafer. Prior to deposition the substrates were manually abraded with 1-3 µm diamond grit, and then cleaned with propan-2-ol.…”
Section: Methodsmentioning
confidence: 99%
“…Previous attempts to make n-type diamond by doping with elements such as N, S or P have either been unsuccessful, or have produced films with electrical characteristics that are not adequate for many proposed devices [1]. However, recent theoretical studies [2,3] have shown that if arsenic or antimony were to be incorporated substitutionally into a diamond lattice, they may act as useful n-type dopants. In particular, these studies predict that substitutional As and Sb should possess significantly shallower donor levels in diamond than substitutional phosphorus, being ~0.4 eV and 0.3 eV below the conduction band minimum, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is the archetypal semiconductor, whereas diamond can be an ideal material for many electronic applications as it has a wide band gap, high carrier mobility, thermal conductivity, and low dielectric constant. [11][12][13] The aim is to compare these two isostructural materials since they have significantly different electronegativities.…”
mentioning
confidence: 99%